Critical race theory : exploring its application to public administration - Riccucci, Norma (Cambridge : Cambridge University Press, 2022)
This Element explores Critical Race Theory (CRT) and its potential application to the field of public administration. It proposes specific areas within the field where a CRT framework would help to uncover and rectify structural and institutional racism. This is paramount given the high priority that the field places on social equity, the third pillar of public administration. If there is a desire to achieve social equity and justice, systematic, structural racism needs to be addressed and confronted directly. The Black Lives Matter (BLM) movement is one example of the urgency and significance of applying theories from a variety of disciplines to the study of racism in public administration.
Title from publisher's bibliographic system (viewed on 21 Feb 2022).
Keywords: Critical race theory; Racism; Public administration -- Social aspects